Information Quality and Information Systems Success: Perspective of Monitoring, Evaluation, Accountability and Learning Information Systems Grounded on DeLone and McLean Model - Andresile, Peter; Tukei, J.M.O.; Alupo, Charity D.; Tukei, Lyn; Edemacu, Kennedy (Research gate, 2022)
As focus has shifted from continuum to contiguum approach of humanitarian response, organizations have invested in Information Systems (IS) to support their Monitoring and Evaluation (M&E), Accountability and Learning (MEAL) functions. The purpose of this study was to assess the influence of information quality on MEALIS performance in humanitarian organizations in developing country context using the widely acclaimed DeLone and McLean (D&M) Model of IS Success (ISS) as the theoretical basis. A cross-sectional research design with mixed approach skewed towards descriptive/quantitative method was adopted for the study. A total of 263 respondents submitted responses to the questionnaire and 3 interviews were conducted. IBM SPSS Statistics was used for descriptive and correlation data analysis and hypothesis testing using Partial Least Squares – Structural Equation Modelling (PLS-SEM) technique using SmartPLS 3 software. The findings of correlation analysis indicated that Pearson’s coefficients (with 1-tailed sig. value of 0.000) ranged from 0.514** to 0.770** for dimensions of information quality construct suggesting significant positive relationship between the independent variable (information quality) and MEALIS success. The hypothesis testing results using PLS-SEM technique revealed that information quality (INQ) was found to be positively related with MEALIS performance with path coefficients, β, of 0.556 (p>0.05). The study concluded that, information quality significantly positively influences the success of MEALIS in humanitarian organizations. It is recommended that
Keywords: Information Quality; Monitoring; Evaluation; Accountability